The perception of selected households in Barangay San Jose Cawa-Cawa, City of Zamboanga on the influenza A(H1N1) health campaign promotional tolls - Fermo, Alkene B.
This communication research was conducted with the goal of knowing the effectiveness of the health communication tools in the prevention and dissemination of information regarding Influenza A(H1N1). The printed communication tools, such as the posters in this study, are predominantly being used by the Department of Health and other health institutions through Barangay Health Centers across the nation I matters relating to health care, health campaign and health promotion. These social artifacts are essential to analyze for it is an important reminder of health habits and practices that should be exercised in the community in curbing cases like Influenza A(H1N1). The study was conducted at Barangay San Jose Cawa-cawa, City of Zamboanga among forty respondents who attended a health seminar on August 2010. The area was selected as research locale for the reason that the Barangay Health Center is actively initiating and working on health campaigns and promotions. The researcher used the Semantic Meaning Theory as conceptualized by Charles Osgood where bipolar adjectives are set upon intervals or scales within the bounds of the receiver's perception on the description of a given any external or social artifact. Moreover, the measurement of an individuals' perception belongs to the metaphorical space of the mind that denotes evaluation, potency and activity. This is the tool used in the extraction of the respondents' perceptions, this is also known as he Semantic Differential Rating Scale or the measurement of the meaning-making process of individuals. The study focused on the perceptions of the forty respondents on the prominence, tone and treatment of the three posters used namely: Poster 1: Takpan ang ilong at bibig. Poster 2: Maghugas ng kamay and Poster 3: Influenza A(H1N1). A survey was conducted using the following adjectives: good ? bad, appropriate ? inappropriate; educational ? not educational, worthless, valuable, satisfactory ? unsatisfactory, entertaining ? not entertaining, colorful ? not colorful, simple, elaborate and vague ? evident. This is based on the three dimensions of the Semantic Meaning Theory. The analysis of the data extracted used descriptive statistical approach where the extraction of the Measure of location, known as the measure of Central Tendency, and the Measure of Dispersion -the Variance and Standard Deviation. This was done by quantifying the variables involved in the survey questionnaire within the ordinal and internal level scales. The mean average rating is essential to acquire the rating that is dominant in the spread of the variables. The forty respondents from Barangay San Jose Cawa-cawa perceive the three communication tools (posters) used in the dissemination of information and prevention regarding the health issue of Influenza A(H1N1) as effective this is based on the results of the parametric statistical tests and the analysis of the central tendency. The results clearly convey that the producers of the health promotional tools, which is the Department of Health, are successful in transmitting the health message across to the members of the community. The results also suggest that the use of the Semantic Meaning Theory's Semantic Differential Rating Scale is effective in the extraction of the respondents' perception regarding the health related effects espoused by the communication tools.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication